Genistein: A Novel Anthocyanin Synthesis Promoter that Directly Regulates Biosynthetic Genes in Red Cabbage in a Light-Dependent Way - Zhang, Na; Qi, Yan; Zhang, Hai-Jun; Wang, Xiaoyun; Li, Hongfei; Shi, Yantong; Guo, Yang-Dong (Frontiers in Plant Science, 2016)
Genistein (GNT), an isoflavone, is used in the clinical treatment of various health disorders. GNT is found in primary food source plants and some medical plants. However, studies on the functions of GNT in plants are rarely reported. In this study, we demonstrated that GNT plays an important role in promoting anthocyanin accumulation in red cabbage. GNT solutions (10, 20, 30, 40, and 50 mg/L) as foliar fertilizers were applied to red cabbage. Consequently, anthocyanin accumulation in red cabbage increased in a light-dependent manner. GNT solution at 30 mg/L exhibited the optimal effect on anthocyanin accumulation, which was twice that of the control. Quantitative real-time PCR analysis indicated that GNT application upregulated the expression of all structural genes, contributing to anthocyanin biosynthesis under light conditions. Under dark conditions, GNT exerted no significant promotive effect on anthocyanin accumulation; only early biosynthetic genes of anthocyanin biosynthesis responded to GNT. The promotive effect of GNT on anthocyanin biosynthesis is directly attributable to the regulation of structural gene expression. Transcription factors exhibited no response to GNT. The levels of anthocyanin in red cabbage positively correlated with the enzyme activities of antioxidant systems. This finding correlation suggested that the promotive effect of GNT on anthocyanin levels was correlated with improved antioxidant activity in the red cabbage.